Pembinaan Kerohanian Anak Melalui Panggung Boneka Bertajuk “Jangan Menangis Papa” di GAIS Gideon Payungan, Semarang - Wahyu Wijiati (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2025)
The background of the Community Service are: First, the reality that many families of believers are less harmonious which has a negative impact for children's development. Second, the condition of children in villages who lack educational entertainment. Third, the decreasing attention of the church to the spiritual development of children because it prioritizes the spiritual development of adults. Therefore, the purpose of this Community Service are: First, to provide solutions to family problems in particular. Second, to provide educational entertainment for children. Third, to involve local churches to take a greater part in the spiritual development of children. The results of this Community Service are that 89% of participants felt very satisfied, 8% of participants felt satisfied, and 3% of participants felt dissatisfied. Thus, the results of this Community Service fall into the category of high level of satisfaction.